2013
DOI: 10.3109/02699052.2012.729291
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the quality of inpatient rehabilitation care to facilitate school re-entry and cognitive and communication function for children with TBI

Abstract: Substantial variations exist in the delivery of paediatric inpatient rehabilitation care processes for managing school re-entry and cognitive and communication impairments after traumatic brain injury. Measures of association of these care processes with patient outcomes are necessary. Reduction in this variation is essential to improving quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In this study, quality indicators such as having pediatric trained providers, adequate specialized pediatric equipment and classrooms were more likely to be present in pediatric rehabilitation facilities. 11,12 Our finding supports the results of the quality indicator study. Further research is needed in order to examine if these child-specific services contribute to the higher discharge scores among children who received care at pediatric rehabilitation facilities.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, quality indicators such as having pediatric trained providers, adequate specialized pediatric equipment and classrooms were more likely to be present in pediatric rehabilitation facilities. 11,12 Our finding supports the results of the quality indicator study. Further research is needed in order to examine if these child-specific services contribute to the higher discharge scores among children who received care at pediatric rehabilitation facilities.…”
Section: Discussionsupporting
confidence: 87%
“…75 The majority of research has described the transition process from hospital to school for hospitalized children. It has been shown that the return to school process is critical to children’s outcome and that successful return to school requires integration between entities, specifically the hospital and the school.…”
Section: Practices Of Carementioning
confidence: 99%
“…Transition from healthcare to school services is also characterized by substantial variability. 75 In the first year after the injury, a substantial portion of children with moderate or severe TBI have unmet (~20%) or unrecognized (~10%) healthcare needs, with cognitive services being the most frequent among these. 11 Reasons for unmet needs include lack of physician recommendation or referral, services not provided in school settings, failure of parent follow-up, and cost.…”
Section: Problems With Current Systems Of Carementioning
confidence: 99%
“…Previous studies demonstrate that even when such services are provided, parents still have difficulties navigating the complicated system of rehabilitation therapies available through clinical and school settings. 23, 24 …”
Section: Discussionmentioning
confidence: 99%